SYNCRETIC ARCHITECTURE OF FATEHPUR SIKRI: A SYMBOL OF COMPOSITE CULTURE - Ali, Asif (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2013)
AbstractThe amalgamation of native Indians and Muslim immigrants eventuated in a prolific way in the realm of literature, art, music, technology and especially in architecture, which reached at its zenith during Mughal period. Akbar, the great Mughal, is greatly recognized for his syncretism and religious tolerance. With the power of his influential personality and eclectic approach, he unified the various artistic traditions and architectural styles in the design of his new capital city, Fatehpur Sikri. Although, the architectural forms and construction techniques involved in the design of city had already been incorporated since the arrival of Islam in Indian subcontinent, but their synthesis reached at its zenith at Fatehpur Sikri and thus traditionally rich and fanciful indian style was merged with the lightness and simplicity of Islamic style. This paper will focus on the unique intermingling of two entirely different styles like their cultures which were born in different regions and with different approaches. This fusion developed a new style in architecture besides several other aspects of life in India.Keywords: Fatehpur Sikri, Mughal Architecture, Composite Culture, Akbar AbstrakPenggabungan India kuno dan imigran muslim menghasilkan banyak literatur, seni, musik, teknologi, dan terutama arsitektur yang mencapai puncaknya selama periode Mughal. Akbar, Mughal yang besar, diakui untuk sinkretisma dan toleransi beragama. Dengan kekuatan pengaruh kepribadiannya dan pendekatan eklektik, dia menyatukan tradisi seni yang bervariasi dan gaya arsitektural pada desain ibukota yang baru, Fatehpur Sikri. Meskipun bentuk arsitektural dan teknik konstruksi terlibat dalam desain kota sudah tergabung sejak kedatangan Islam di India, tapi perpaduannya mencapai puncaknya pada Fatehpur Sikri, jadi gaya India yang fantastis dan kaya secara tradisional digabung dengan kesederhanaan gaya Islam. Artikel ini akan fokus pada pembauran yang unik pada dua gaya yang berbeda seperti budaya yang lahir pada daerah yang berbeda dengan pendekatan yang berbeda. Peleburan ini mengembangkan gaya baru dalam arsitektur di samping beberapa aspek kehidupan yang lain di India. Kata kunci: Fatehpur Sikri, Arsitektur Mughal, Budaya Komposit, Akbar